Communications 1990: A Report of the Future Committee; The Misutilization of Evaluation Research: Some Pitfalls of Definition; Searching for Alternatives: Public Broadcasting - Larry Meiller; John Fett (Journal of Applied Communications, 1980)
Reviews of Communications 1990: A Report of the Future Committee; "The Misutilization of Evaluation Research: Some Pitfalls of Definition," by Thomas Cook , Judith Levinson-Rose and William Pollard; "Searching for Alternatives: Public Broadcasting ," Journal of Communication.